THE INFLUENCE OF DESTINATION BRANDS, TOURIST FACILITIES, AND BRAND ATTACHMENTS TOWARDS BRAND LOYALTY OF VISITORS TO THE ACEH TSUNAMI MUSEUM - Siti Nur Balqis Qhomaini; Mariyudi; Agustinawati; Muchsin (RADJA PUBLIKA, 2024)
This research aims to analyze the influence of brand destinations, tourist facilities and brand attachments on the brand loyalty of visitors to the Aceh Tsunami Museum. Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The respondents in this research were 100 visitors to the Aceh Tsunami Museum. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The research results show that partially the Destination Brand has a positive and significant effect on the Brand Loyalty of Visitors to the Aceh Tsunami Museum. Partially, tourist facilities have a positive and significant effect on brand loyalty for visitors to the Aceh Tsunami Museum. Partially, Brand Attachment has a positive but not significant effect on Brand Loyalty for Visitors to the Aceh Tsunami Museum. Simultaneously, it shows that the Destination Brand, Tourist Facilities, and Brand Attachments have a significant influence on the Brand Loyalty of Visitors to the Aceh Tsunami Museum.